2020
DOI: 10.1016/j.legalmed.2019.101665
|View full text |Cite
|
Sign up to set email alerts
|

Facial average soft tissue depth variation based on skeletal classes in Indonesian adult population: A retrospective lateral cephalometric study

Abstract: Highlights • Database of 10 midline facial landmarks average soft tissue thickness grouped into 3 skeletal classes in Indonesian adult population is presented in this study. • Significant difference among skeletal classes occurred in male lower lip. • Significant differences among skeletal classes occurred in female subnasale, upper lip, stomion, lower lip and labiomentale. • A generic pattern of deeper upper lip than lower lip in class III compared to class II and conversely, deeper lower lip than upper lip i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
12
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 46 publications
6
12
0
8
Order By: Relevance
“…In addition, the five upper lip characteristics in Class III group changed inversely to that in Class II. It is conceivable that upper lip length increases due to maxillary overgrowth, and upper lip thickness augments in cases with maxillary retrusion due to soft tissue compensation, which is also confirmed by previous studies in other countries [ 5 , 32 , 33 ]. However, the significant decrease in nasolabial angle from Class II to Class III was contradictory to previous studies, including Burstone’s perspective that decreased nasolabial angle indicated maxillary protrusion [ 31 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, the five upper lip characteristics in Class III group changed inversely to that in Class II. It is conceivable that upper lip length increases due to maxillary overgrowth, and upper lip thickness augments in cases with maxillary retrusion due to soft tissue compensation, which is also confirmed by previous studies in other countries [ 5 , 32 , 33 ]. However, the significant decrease in nasolabial angle from Class II to Class III was contradictory to previous studies, including Burstone’s perspective that decreased nasolabial angle indicated maxillary protrusion [ 31 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 83%
“…Accumulated evidence has demonstrated that both sagittal and vertical skeletal patterns greatly impact on soft tissue morphology [ 2 , 3 , 4 ]. For instance, a study on an Indonesian population found that the upper lip was generally deeper in Class III compared to Class II [ 5 ]. Similarly, it was shown that facial soft tissue thickness, especially in the chin area, varied among different vertical developmental patterns, which was smaller in hyperdivergent patterns [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal classification was performed by ANB angle, 15,22,24 which indicates the relations between maxilla and mandible. Another anterior-posterior index measured in this study was A-B plane to facial plane angle.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Anterior-posterior skeletal classifications: in orthodontics, people are classified into three skeletal classes based on the anatomical relationship between maxilla and mandible 14 and Various studies have reported differences in soft tissue thickness in similar races among these three classes. 15,16 Edward Angle classified dental malocclusion into four classes, namely normal malocclusion, class I malocclusion, class II malocclusion and class III malocclusion. 17 This classification can also be used for patients' skeletal conditions based on the anterior-posterior position of the maxilla and mandible relative to one another.…”
mentioning
confidence: 99%
“…Data on women who occupied the DPR seats in 1999-2004 were 46 (9%), men 500 (91%), while in 2004-2009 women were 61 (11.09%) and 489 men (88). ,9%) (Kobayashi et al, 2011); (Sarilita, Rynn, Mossey, Black, & Oscandar, 2020).…”
Section: Barometer Global Corruptionmentioning
confidence: 99%